Polarized and Pyramidal Training Intensity Distribution: Relationship with a Half-Ironman Distance Triathlon Competition - Selles-Perez, Sergio; Fernández-Sáez, José; Cejuela, Roberto (Journal of sports science & medicine, 2019)
The purpose of the present study was to relate the training intensity distribution with performance in a Half-Ironman distance triathlon competition. A total of 18 recreational-level triathletes were divided into two training groups according to their training intensity distribution: Polarized (POL) and Pyramidal (PYR). Prior to the specific training period of the study, subjects performed a ramp-protocol test, running and cycling to determine ventilatory thresholds (VT) through gas-exchange analysis. For swimming, subjects performed an 800-metre test to establish their training zones. Training was quantified based on the cumulative time spent in 3 intensity zones: zone 1 (low intensity, <VT1), zone 2 (moderate intensity, VT1-VT2) and zone 3 (high intensity >VT2). POL competed 84.5%/4.2%/11.3% and PYR 77.9%/18.8%/3.3% of total training time for zones 1,2 and 3 respectively. The goal of the training period was a half Ironman distance triathlon. Training time in zone 2 inversely correlated with swimming and cycling race time in POL and with running and total race time in PYR. Power at VT2 on bike and speed at VT2 as well as maximum aerobic power and speed in the physiological post test inversely correlated with bike and run segment respectively and with total race time. These results suggest that training time in zone 2 was related with better performance on a Half-Ironman race in amateur triathletes. Future experimental research is needed to clarify the importance of training intensity distribution regarding performance.